Upgrading Community Capability In Treating Domestic Wastewater Through Training on Making Simple Grease Traps - Roslinda Ibrahim; Mary Selintung; Achmad Zubair; Nur An-nisa Putri Mangarengi; Nurjannah Oktorina Abdullah; Syarifuddin Syarifuddin (Faculty of Engineering UNHAS, 2023)
Oil and grease are one type of waste that has not been handled properly. If this waste is discharged into the environment without going through a treatment process, it can cause blockages in the pipeline and pollution in the waters. Waste oil and fat treatment can be applied in households, but it is still constrained by the selection of simple, cheap, and easy-to-apply processing technology. The purpose of this activity is to increase the knowledge of the people of Romanglompoa Village regarding the types of technology that can be used to treat waste oil and fat and to improve people's skills in making grease traps. The method used to achieve the goals and targets that have been set is by carrying out training activities on making simple grease traps in community residential areas. The counseling activity was carried out at the Romanglompoa village office and attended by thirty participants. The enthusiasm of the participants was very high in participating in the counseling, this can be seen from the seriousness in receiving the material and the desire to ask questions during the activity. The post-test results showed that 50% – 64% of participants understood the counseling material which included the impact of waste oil and fat on the environment, the types of technology that can be used to treat waste oil and grease, and improve community skills through training activities on making simple grease traps.